A Pandemic’s Punitive Pedagogy: Education and the Organic Crisis of the Global Neoliberal Order - McKay, Ian (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2021)
The Covid-19 pandemic entailed a cruel pedagogy with regard to neoliberalism. Neoliberalism embodies a multifaceted process whereby the post-1945 Fordist compromise was gradually transformed, after the mid-1970s, into a world order privileging business competition, both as a daily practice and a philosophy of rule. This order has been enmeshed in an “organic crisis” since 2007-08, which has progressively revealed neoliberalism’s problematic status in relation not only to the practice of democracy, but to the survival of the species. This article focuses specifically on the ways in which the pandemic has not only illuminated neoliberalism’s core contradictions, but portends their intensification and widening impact.